Studies on Mn(II), Co(II), Ni(II) and Cu(II) Complexes of Schiff Bases Derived from Furfurylimine with Benzaldehyde and Phenyl Glyoxal - Kumar, Adesh; Das, Shanu; Dhakarey, Rajesh (Asian Journal of Chemistry, 2010)
All the complexes of Mn(II), Co(II), Ni(II) and Cu(II) with Schiff bases furfurylimine of benzaldehyde (FIB) and furfurylimine of phenyl glyoxal (FIPG) were synthesized and characterized on the basis of elemental analysis, magnetic moment values, NMR, mass, infrared and electronic spectral studies. The infrared spectral data suggests that the ligand coordinates via furan and glyoxalic oxygen and azomethine nitrogen. The coordination of chloride ion were also found in the complexes. The magnetic moment values and electronic spectral data indicate six coordinate geometry around the metal ion. In the case of Cu(II) complexes ESR spectral studies have also been taken place. The biological screening was carried out against P. aeruginosa, A. niger and A. flavous suggests strong antimicrobial activities.